Hak Perempuan Berpolitik Dalam Perspektif Hukum Islam - Yulia Ibrahim; Nur M Kasim; Suwitno Y Imran (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
The representation of women in politics has become a much discussed issue along with the development of political access. Various factors are the cause of this, including religious factors. The purpose of this study is to be able to determine and analyze women's political rights in the perspective of Islamic law. This study was conducted using the type of normative legal research with two types of approaches, namely the statutory approach (Statute Approach) and conceptual approach (Conceptual Approach). Based on research that researchers have done, the results obtained that islam recognizes the existence of women's political rights and the importance of the role of women in public life and its impact on political life.